ANALISIS KEBUTUHAN BAHAN AJAR BAHASA INDONESIA BERBANTU MULTIMEDIA QR CODE UNTUK SISWA KELAS IV SEKOLAH DASAR - Haryanto, Henzi; Suyitno, Imam; Anggraini, Ade Eka (Universitas Tanjungpura, 2025)
This research was conducted in order to see the shortcomings of the need for diverse teaching materials and has not been used as a whole in elementary schools. This limitation is the impetus for educators to develop interactive and innovative media, one of which is developing QR-Code assisted flipbook media in Indonesian language subjects with